Moderate to severe hidradenitis suppurativa patients do not have an altered bacterial composition in peripheral blood compared to healthy controls. (12th September 2017) - Ring, H.C.; Thorsen, J.; Saunte, D.M.; Lilje, B.; Bay, L.; Theut Riis, P.; Larsen, N.; O'Brien Andersen, L.; Vedel Nielsen, H.; Miller, I.M.; Bjarnsholt, T.; Fuursted, K.; et al.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease defined by recurrent nodules, tunnels and scarring involving the intertriginous skin. Patients with HS often report an array of systemic symptoms such as fatigue and malaise. The aetiology of these symptoms remains unclear. Previously, various bacteria have been associated with mature HS lesions, and bacteraemia has been reported in patients with HS using traditional culturing methods. Thus, we hypothesized that a low‐grade bacteraemia contributes to the symptomatology in patients with HS. Objective: To explore the potential presence of bacteraemia in patients with HS and healthy controls. Method: A case–control study. Compositions of bacteria in the blood of 27 moderate to severe HS patients and 26 healthy controls were investigated using next‐generation 16S ribosomal RNA gene sequencing (NGS) and routine anaerobic and aerobic blood culturing. None of the participants received any antibiotics (systemic or topical therapy) within 1 month prior to the study. HS patients with a recent flare were randomly selected by consecutive recruitment of eligible patients from the Department of Dermatology, Zealand University Hospital, Denmark. Healthy controls were recruited from the University of Copenhagen as well as from the healthcare staff. Results: The different bacterial compositions were investigated using NGS and traditional anaerobic and aerobic blood culturing. Our NGS analysis provided a previously unreported characterization of the bacterial composition in peripheral blood from patients with HS and healthy controls. Overall, our data demonstrated that patients with HS do not have a different bacterial composition in their peripheral blood than healthy controls. Conclusion: The study suggests that the self‐reported symptoms in HS such as malaise and fatigue may not be linked to bacteraemia.